Significance of mammalian N, N-dimethyltryptamine (DMT): A 60-year-old debate - Jiménez, Javier Hidalgo; Bouso, José Carlos (Journal of psychopharmacology (Oxford), 2022)
N,N-dimethyltryptamine (DMT) is a potent psychedelic naturally produced by many plants and animals, including humans. Whether or not DMT is significant to mammalian physiology, especially within the central nervous system, is a debate that started in the early 1960s and continues to this day. This review integrates historical and recent literature to clarify this issue, giving special attention to the most controversial subjects of DMT's biosynthesis, its storage in synaptic vesicles and the activation receptors like sigma-1. Less discussed topics, like DMT's metabolic regulation or the biased activation of serotonin receptors, are highlighted. We conclude that most of the arguments dismissing endogenous DMT's relevance are based on obsolete data or misleading assumptions. Data strongly suggest that DMT can be relevant as a neurotransmitter, neuromodulator, hormone and immunomodulator, as well as being important to pregnancy and development. Key experiments are addressed to definitely prove what specific roles DMT plays in mammalian physiology.